Build Android apps with App Inventor 2 : no coding required - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2015)
"Everybody has a great idea for an app. The problem is, not many of those people have the skills or knowledge required to make that idea a reality. Building an app, regardless of its simplicity or platform, requires certain technical know-how like coding, UX/UI design, and more. App Inventor 2, however, cuts through all of the smoke and allows anyone--even those with no coding experience--to build Android apps from the ground up. This course will teach you how. This course will teach you everything you need to know about building apps--without the complicated coding normally required. If you have a good internet connection, a basic understanding of what an Android app is, and a great idea for an app that doesn't yet exist, then you're the perfect candidate! While the course is aimed at beginner programmers or those with no coding experience whatsoever, experienced app builders who want to learn from a new angle will benefit too."--Resource description page.
Title from resource description page (viewed January 19, 2016).
Keywords: Mobile apps -- Development; Android (Electronic resource); Electronic books